The global burden of maternal disorders attributable to iron deficiency related sub-disorders in 204 countries and territories: an analysis for the Global Burden of Disease study - Nuer Wu; Erdengqieqieke Ye; Yulan Ba; Shareli Caikai; Bayinsilema Ba; Ling Li; Qiying Zhu (Frontiers Media S.A., 2024)
BackgroundPregnancy-related anemia presents a significant health concern for approximately 500 million women of reproductive age worldwide. To better prevent maternal disorders, it is essential to understand the impact of iron deficiency across different maternal disorders, regions, age groups, and subcategories.MethodsBased on the comprehensive maternal disorders data sourced from the 2019 Global Burden of Disease study, an investigation was carried out focusing on Disability-Adjusted Life Years (DALYs) associated with iron deficiency spanning the period from 1990 to 2019. In addition, Estimated Annual Percentage Changes (EAPCs) were computed for the duration of the study.ResultsOur study indicates decreasing mortality rates and years of life lost due to maternal conditions related to iron deficiency, such as maternal hemorrhage, miscarriage, abortion, hypertensive disorders, and infections. However, mortality rates and years of life lost due to indirect and late maternal deaths, as well as deaths aggravated by HIV/AIDS, have increased in high socio-demographic index (SDI) regions, especially in North America. Moreover, the proportion of maternal deaths aggravated by HIV/AIDS due to iron deficiency is rising globally, especially in Southern Sub-Saharan Africa, Oceania, and Georgia. In addition, in the Maldives, the age-standardized DALYs for maternal disorders attributable to iron deficiency exhibited a notable decreasing trend, encompassing a range of conditions. Furthermore, there was a significant decrease in Disability-Adjusted Life Years rate for miscarriages and preterm births among women aged 15-49, with hypertensive disorders posing the highest burden among women aged 15-39.ConclusionThe burden of maternal disorders caused by iron deficiency is decreasing in most regions and subtypes, except for deaths aggravated by HIV/AIDS. By thoroughly understanding the details of how iron deficiency impacts the health of pregnant women, health policymakers, healthcare professionals, and researchers can more effectively pinpoint and address the root causes of inequalities in maternal health.